PENGARUH LIMBAH AMPAS SAGU YANG DIKOMPOSKAN DENGAN AKTIVATOR BERBEDA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TERUNG (Solanum melongena L.) - Elisa Apriliani; Idwar Idwar; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
One of the efforts to increase the production of eggplant in an intensified manner is to balance fertilization. This study aims to determine the effect of giving sago pulp compost with different activators, as well as the best treatment in increasing the growth and production of eggplant. The research was carried out at UPT Faculty of Agriculture, University of Riau in May to August 2018 experimentally using a Completely Randomized Design (CRD) consisting of six treatments and three replications. Treatment includes S0 = Without compost, S1 = Sago waste, S2 = Compost sago waste with chicken manure activator, S3 = Compost sago waste with EM4 activator, S4 = Compost sago waste with Trichoderma activator, and S5 = Compost sago waste with Bacillus activator, each of 5 tons.ha-1 or 1,26 kg per 2,52 m2. The observed parameters included total N, total P, total K, pH, organic C, plant height, stem diameter, flowering day, harvest day, fruit weight, fruit diameter, fruit length, fruit weight per plant, number of fruits per plant, and production per plot on eggplant. The results showed that the nutrient content of N, P, K from the compost use each activator results had met the SNI compost quality standard (2004). Sago waste compost fertilizer with activator EM4 has a best chemical content of pH value 7.12, N-total 0.92%, P-total 1.26%, K-total 1.16% and C/N 33.54 and compost was able to increase fruit weight, fruit diameter, fruit length, fruit weight per plant, number of fruits per plant and production per eggplant plot. Compost of sago waste with chicken manure activator (5 ton.ha-1) was able to increase the growth of plant height and stem diameter of eggplant.Keywords: Compost, Sago waste, Activator, Eggplant, Quality of compost